Development and the environmental crisis: red or green alternatives - Redeclift, Michael (London, 1991)
This important new book makes the global environmental crisis a central concern of political economy and its structural causes a central concern of environmentalism. Although there is a growing recognition of the environmental crisis facing the South - triggered by the Brandt Report's North-South debate and the concern with the tropical environment set out in the World Conservation Strategy - the environment is rarely interpreted within the framework of global economic relations, nor does it form part of most current analyses of underdevelopment. Through his review of Europe's Green Movement, recent breakthroughs in biotechnology and information systems and recent feminist discourse, Michael Redclift has enlarged the compass of the environmental debate and produced a book which should serve as a benchmark in future discussions of development and the environment.
Keywords: Environmental policy